Penerapan Digital Branding Dalam Meningkatkan Upaya Pemasaran Pada UMKM Abon Lele Desa Dersalam - Octavia, Putri Nabila; Damayanti, Anisa Iqlima; Sumartono, Thalia Chandra Dewi; Afariyanto, Vigo Ade; Kusuma, Chrestella Putu Holy; Maharani, Shinta Fanindia; Jayasanti, Renny Adi; Artiarno, Andrean Maulana (Jurnal Muria Pengabdian Masyarakat, 2025)
Muria Kudus University's Thematic KKN Program focuses on branding MSMEs, including shredded lele MSMEs in Dersalam Village which are managed by local residents. The main issue faced is the lack of knowledge and skills in promoting shredded catfish products, making it difficult to compete in the wider market. The focus of this service is to improve community capabilities in branding and product promotion strategies. The aim of the service is to strengthen the identity and appeal of shredded catfish products through training and assistance in digital and offline marketing. The methods used include branding workshops, creating promotional content, and using social media. The results of the service show an increase in public awareness and ability to market products, an increase in sales of shredded catfish, and the introduction of products to a wider market. This program has succeeded in having a positive impact on the economic development and independence of the Dersalam Village community.